The Impact of Inflation, Interest Rates, and Exchange Rates on the Jakarta Composite Index - Eric, Eric; Hikmah, Khoirul (CV. Strata Persada Academia, 2025)
This study aims to analyze the response of the Jakarta Composite Index (JCI) to macroeconomic variables, namely inflation, interest rates, and exchange rates, during the 2018–2024 period. Understanding the relationship between these variables is crucial for investors, policymakers, and financial analysts in making informed decisions regarding stock market movements in Indonesia. The research utilizes secondary data on JCI, inflation, interest rates, and exchange rates sourced from Bank Indonesia and the Indonesia Stock Exchange. The data is analyzed using the Vector Error Correction Model (VECM) to capture short-term and long-term dynamics. The findings indicate that inflation and interest rates do not significantly influence JCI, suggesting that stock market participants may have already factored in these macroeconomic variables. Meanwhile, exchange rates demonstrate a significant positive long-term effect on JCI, implying that currency fluctuations are crucial in shaping stock market performance. These results provide valuable insights into the interplay between macroeconomic indicators and the stock market, highlighting the importance of exchange rate stability in fostering a favorable investment climate.